Parish Catechesis. Current State and Challenges - Zellma, Anna (Studia Warmińskie, 2024)
This study attempts to identify the current state of parish catechesis in the opinion of catechists from various dioceses in Poland. The analysis was conducted based on empirical material obtained from survey questionnaires sent electronically through the directors of catechetical papers/departments of diocesan curia to all catechists in Poland (985 completed questionnaires were received). The results of the survey made it possible to diagnose the current state and challenges of parish catechesis. The hypothesis was confirmed: parish catechesis in Poland does not cover all its forms; in fact, it is centered around sacramental catechesis. The vast majority of catechists are involved in the parish in various forms of catechesis that prepare children and adolescents for the sacraments of Christian initiation. Respondents declared that they conduct meetings for children and youth and their parents related to preparation for the sacraments of Christian initiation. A high percentage of catechists had positive experiences related to cooperation with the pastor in the parish where they worked. The respondents also indicated the need for various forms of adult catechesis in the parish, especially evangelization meetings, biblical meetings, formation meetings, carried out in small groups. The experience of catechists in parish catechesis is a reliable source of information that can be used in the future to revitalize and improve parish catechesis.